Ballot box biology and how communication constructs conservation in Colorado's wolf reintroduction - Camara, Cassiopeia C., author; Gallo-Cajiao, Eduardo, advisor; Crooks, Kevin, committee member; Anderson, Ashley, committee member; Salerno, Jon, committee member (Colorado State University. Libraries, 2026)
What secures conservation once a democratic decision has been made? Contemporary conservation disputes are often described as battles over evidence or ideology but formal approval does not automatically settle questions of legitimacy, as authorization marks a decision point, not necessarily the end of contestation. This dissertation examines how communication operates at various stages of a conservation decision lifecycle and gains insights into whether and how legitimacy progresses in tandem. The case study used throughout the dissertation is that of Colorado's wolf (Canis lupus) reintroduction, the first large carnivore reintroduction in the United States directed by popular vote. Chapter Two analyzes 193 newspaper articles published prior to the 2020 ballot initiative to identify dominate arguments, rationales and patterns before democratic authorization occurred. Chapter Three then analyzes 321 articles from the implementation period (from when Proposition 114 passed to when wolves were released) which generated 3,220 coded statements to assess how governance dimensions (i.e., legitimacy, justice and multi-level governance) were espoused as the narrow voter mandate moved into administrative action. Chapter Four examines youth survey responses using hierarchical thematic coding to explore how young people think about and make sense of conflict, coexistence and their willingness to share information. Results reveal that authorization occurred within a media environment where opposition to wolf reintroduction narrative was more numerous and more varied than those in support of reintroduction. Narratives opposing wolf reintroduction used a variety of framing including economic risk, rural identity, government distrust and even salient issues of the time like Covid-19, while narrative of coverage in support of reintroduction relied primarily on ecological reasoning. During the implementation phase, legitimacy overshadowed governance related reporting and frequently anchored claims about fairness and expectations. Justice only appeared in association with legitimacy and multi-level governance was most often linked to concerns of credibility and authority. Among youth, ecological understanding was high but did not transfer into communication and youth willingness to share information was dependent on perceived audience receptivity and relational proximity more than on belief or knowledge strength alone. These studies collectively identify a persistent tension in democratic conservation that procedural approval does not guarantee durable acceptance and aims to clarify how conservation legitimacy is interpreted as decisions move across different democratic phases and social contexts. Communication across this dissertation is not peripheral to these processes; it is woven into each stage how conservation decisions are interpreted and sustained.
Keywords: conservation communication; media narratives; species reintroduction; democratic governance; coexistence; policy implementation